Analysis of Lavender Aroma and Guided Imagery on Insomnia in Lansia in Technical Specific Unit Social Tresna Wherda Glenmore District Banyuwangi - Grenda Aprilyawan (Journal for Quality in Public Health, 2019)
Naturally the elderly is experiencing a decline both in terms of physical, biological and mental and this is not independent of economic, social and cultural issues. Sleep disorders is one of the health problems often faced by the elderly. The elderly require good sleep quality to improve health and restore the condition of the illness. There are several ways to deal with insomnia can be done in 2 ways: pharmacology and non pharmacology. The purpose of this study was to determine the effect of lavender and guided imagery on insomnia in elderly in Technical Implementation Unit (UPT) of Social Tresna Werdha Glenmore Sub-district of Banyuwangi Regency. In this research, the research design used is True experimental research design. The population of the study were all elderly people who experienced insomnia of 36 people and sample of 33 people by using simple random sampling. Data collection using checklist sheet then analyzed using Cochran test. The results showed that significant probability value of Cochran test of 0,032 <0,05 means there is significant difference between giving of lavender scent, guided imagery and control group to insomnia. While the treatment before and after the lavender scent there is a significant influence on insomnia (p: 0.008 <0.05). Treatment before and after guided imagery there is a significant effect on insomnia (p: 0,016 <0,05). Treatment before and after the control group there was no significant effect on insomnia (p: 0,500> 0,05). Based on the results of this study non pharmacology treatment can be maintained and continued for better sleep quality. Whether using aroma therapy or guided imagery lavender because it has been proven to reduce insomnia.